The CONCEPTION OF ENERGY CRISIS : A CROSS-SECTIONAL STUDY - Putri Sekar Melati (International Conference on Education, Science, Technology and Health (ICONESTH), 2024)
The purpose of this cross-sectional study is to examine how junior high school students and elementary students perceive crisis energy. An online survey, an open-ended inquiry, is used to distribute the instrument. There were 167 research participants, and the percentage included sixth-grade elementary students (14), seventh-grade students (51), eighth-grade students (6), and ninth-grade students (96). The study's findings indicated that ninth-grade students generated the most significant number of concepts, followed by eighth- and seventh-grade students. Students in the ninth grade proposed the idea that